ISLAMIC BOARDING SCHOOL STRATEGY FOR LIFE RELIGION FOR SOCIETY TEGAL BREKAT SUPPORT - Tazali, Imam; Ma’ruf, Amar; Basa, Putie Maharani; Lidwan, Nanang; Lahat, Mohammad Amas; Zulfa, Puspa Fortuna (Jurnal Konseling Pendidikan Islam, 2024)
Education should produce the next generation through Islamic boarding schools who have the character to take control of the state. It is hoped that it will produce the next generation with strong character to accept the baton of leadership. Education has an important role in shaping society, especially among teenagers who are experiencing changes in themselves. With education at an Islamic boarding school, we can overcome moral problems in teenagers, although not completely, and reduce the problems that are currently troubling a country. There are many worries among educators that internal and external factors are not in control of teenagers' education. One external factor that appears and is very influential is smartphones, which can open sites that are not educational, and an internal factor is the lack of attention of parents towards their children.